2 - Principles and Policies Guiding Current Reforms in Nigerian Universities - Okebukola, Peter (Journal of Higher Education in Africa, 2006)
This paper is an attempt to put forward and analyze the principles and politics guiding the reforms currently taking place within the higher education sub-sector in Nigeria. The paper is in three main sections. The first section presents an overview of the Nigeria university system highlighting its problems and challenges. The sec- ond examines the policies and reforms that have been introduced to address the challenges and problems facing the Nigerian university system within a global con- text, including the principles guiding these policies and reforms. The third section is a preliminary attempt to briefly assess the success and sustainability of these reforms. Keeping in mind that it is still early days, and that such far-reaching re- forms will take time to achieve their objectives, I argue that the reforms are already showing evidence of the desired results. Thanks to the reform programme, the Ni- gerian university system is on the road to recovery after many years of neglect.